Semiotics In a Collection of Poetry Book Khong Guan's Banquets by Joko Pinurbo - Zulfa Azhari Ghozali, Muhammad; Hasan, Ikhwanul; Syahfarezi, Garin (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
Semiotics is the study of signs and everything that relates to them. In this case, researchers conducted a semiotics study of Joko Pinurbo's collection of Khong Guan banquets because the poems collected in it contained a rich social, family, and greed wrapped in a witty nature. The signs appearing in the poem collection were analyzed by a semiotics approach of Charles Sanders Peirce using a second systemic trixonics, indexes, and symbols. The study is to describe the semiotical marks of Joko Pinurbo's banquet poem by Joko Pinurbo. The method in this study uses analysis descriptive analytics methods. Analysis techniques in the study use hermeunitika analysis techniques. The source of the data in the study is Joko Pinurbo's collection of Khong Guan banquet poems based on the 22 poems found in the fourth can find Khong Guan.